2022
DOI: 10.1002/hsr2.849
|View full text |Cite
|
Sign up to set email alerts
|

Current situation of shared decision making in osteoporosis: A comprehensive literature review of patient decision aids and decision drivers

Abstract: Background and Aims Osteoporosis is a systemic skeletal disease characterized by low bone mass and microstructural deterioration of bone tissues, resulting in bone fragility and increased fracture risk. It is the most common bone‐related disease in the population. However, the proportion of patients who start treatment but discontinue it during the first year is very high (around 50%). Endeavors are made to promote patient participation in treatment by implementing patient decision aids (PDA), who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 72 publications
0
6
0
2
Order By: Relevance
“…In addition, the authors found that the available decision aids did not comprehensively meet international quality standards and patient needs. Later, Nogues et al [ 23 ] reported that only five decision aids in the field of osteoporosis could be deemed to be completely comprehensive, as they effectively deliver pertinent information about the disease and present viable treatment options to patients. Therefore, the development of new tools and new decision aids is crucial for the field of osteoporosis and fracture prevention.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors found that the available decision aids did not comprehensively meet international quality standards and patient needs. Later, Nogues et al [ 23 ] reported that only five decision aids in the field of osteoporosis could be deemed to be completely comprehensive, as they effectively deliver pertinent information about the disease and present viable treatment options to patients. Therefore, the development of new tools and new decision aids is crucial for the field of osteoporosis and fracture prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is a disease without any pathognomonic clinical signs, which usually remains undiagnosed until a pathological fracture or fracture occurs as a result of lowforce exposure (de Souza 2010; Nogués et al 2022). An osteoporotic fracture, usually affecting the hip and spine, affects a person's performance and normal functioning, leading to chronic pain and long-term rehabilitation (Vidal et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…anti-sclerostin antibodies (romozozumab), strontium ranelate and parathyroid hormone analogues (Tabatabaei-Malazy et al 2017;Camacho et al 2020;Nogués et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Decision aids may improve understanding of potential benefits and harms of preventive treatment 55 57 and shared decision-making could better align screening and treatment with patient preferences. 58 60 …”
Section: Recommendationsmentioning
confidence: 99%
“…Risk assessment–first screening may be acceptable given an increased emphasis on shared decision-making. 60 , 63 , 64 However, access to family physicians and BMD testing varies by age, region (rural and remote v. urban areas), socioeconomic status and race or ethnicity. 65 – 67 In 2015, 11% of Canadian females aged 65–79 years received a BMD.…”
Section: Recommendationsmentioning
confidence: 99%